The importance of order in the theological discussion - Smith, Timothy L. (Sapientia, 1999)
Thomas' doctrine of God in the first part of his Summa Theologiae is a carefully developed construction of a theological grammart. It is properly read according to its own development with each article contextualized within Thomas' increasingly precise terminology and distinctions. For that reason, the precision of Thomas' theological terminology in one section cannot be imported into another, especially into an earlier one. Contrary to the commentary of Cajetan and modern criticisms dependent upon that commentary, Thomas is not and cannot be discussing an absolute, concrete essence in Summa Theologiae I, qq. 2-26. The subject of the discussion is the divine essence2, unum et trinum, not separated from relations and Persons, nor absolutized as a monopersonal God, nor the Person of the Father as unoriginate fount and unity of the Godhead. The essentia of the explicitly trinitarian questions (ST 1, qq. 27-43) is then not the same as the essentia of the earlier questions. In an effort to demonstrate this thesis and its implications for a more sympathetic reading of Thomas' Trinitarian teaching, our procedure in this article will be 1) to elucidate the development of Thomas' use of essentia and why it is necessary to postpone the distinction between essence and person until q. 39; and 2) to analyze the way in which Thomas constructs his Trinitarian grammar and malees use of various terms as he fills out the discussion of the distinction and unity of divine Persons.